Path Planning for Rescue Vehicles via Segmented Satellite Disaster Images and GPS Road Map - Korkmaz, S. Aytac; Poyraz, M. (Ieee, 2016)
One of the most important issues after so many disasters, besides communication determine the damage caused by the disaster areas to reach a moment ago. The emergency rescue teams established for this purpose by making plans to take action on realistic maps are required. Not just as an ambulance during rescue, vehicles in a variety of business machines correct route to take on the road safely. In this study, the image taken before and after the disaster has been segmented. Each segment with one another emerging feature-based compared using statistical methods and information theory. Then we get a measure to path planning using Kullback-leibler distance. Consequently, create a new hazard map is obtained. This map is compared with using the existing path in a city map. In this way, the shortest and safest route to the destination is obtained.
9th International Congress on Image and Signal Processing, BioMedical Engineering and Informatics (CISP-BMEI) -- OCT 15-17, 2016 -- Datong, PEOPLES R CHINA
Keywords: Rescue vehicles; satellite disaster images segmentation; Kullback-Leibler; disaster detection and classification; optimum road estimation; Road Map